PERSEPSI MASYARAKAT DAN AKUNTAN TERHADAP ETIKA PROFESI AKUNTAN - MUINDRO RENYOWIJOYO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2005)
This research examines the different perception of profession ethic of accountant between business communities and accountants. The objective of the research is to explore and empirically examine the different of accounting manager and staff and accountants in their perception of profession ethic of accountant. The samples consist of some companies located in Jakarta. The analysis was based on response from 80 respondents, and data were collected by using questionnaires. Then the hypothesis was tested using ANOVA. Result indicated that there was difference perception of profession ethic of accountant between public accountant and government accountant, and government accountant and internal accountant. There was no difference perception of profession ethic of accountant between public accountant and internal accountant, public accountant and business community, and government accountant and business community. Hypothesis 1 and hypothesis 2 were accepted, but hypothesis 3, hypothesis 4 and hypotesis 5 were rejected.